The Impacts of Feed-in Tariffs on Innovation: Empirical Evidence from Germany - Christoph Böhringer; Alexander Cuntz; Dietmar Harhoff; Emmanuel Asane Otoo (Center for Economic Studies and ifo Institute (CESifo), 2014)
Feed-in tariffs under the Renewable Energy Sources Act, the so-called Erneuerbare-Energien-Gesetz (EEG), have triggered a massive expansion of electricity from renewable energy sources in Germany over the last decade. The increase in non-competitive renewable power generation though went hand in hand with a substantial rise in electricity prices with consumers paying for the renewable energy subsidies. The high cost burden has provoked an intense public debate on the benefits of renewable energy promotion. In this paper, we assess one popular justification for feed-in tariffs, i.e., induced innovation as a positive spillover externality. Based on regressions with a time-technology fixed effect negative binomial model, we find that innovation impacts of feed-in tariffs under the EEG are insignificant.
Keywords: C23; H23; O38; 330; renewable energy promotion; feed-in tariffs; innovation; negative binomial regression